Senescence in dahlia flowers is regulated by a complex interplay between flower age and floret position - Casey, Matthew; Marchioni, Ilaria; Lear, Bianca; Cort, Alex P.; Baldwin, Ashley; Rogers, Hilary J.; Stead, Anthony D. (Frontiers in Plant Science, 2023)
Mechanisms regulating flower senescence are not fully understood in any species and are particularly complex in composite flowers. Dahlia (Dahlia pinnata Cav.) florets develop sequentially, hence each composite flower head includes florets of different developmental stages as the whole flower head ages. Moreover, the wide range of available cultivars enables assessment of intraspecific variation. Transcriptomes were compared amongst inner (younger) and outer (older) florets of two flower head ages to assess the effect of floret vs. flower head ageing. More gene expression, including ethylene and cytokinin pathway expression changed between inner and outer florets of older flower heads than between inner florets of younger and older flower heads. Additionally, based on Arabidopsis network analysis, different patterns of co-expressed ethylene response genes were elicited. This suggests that changes occur in young inner florets as the whole flower head ages that are different to ageing florets within a flower head. In some species floral senescence is orchestrated by the plant growth regulator ethylene. However, there is both inter and intra-species variation in its importance. There is a lack of conclusive data regarding ethylene sensitivity in dahlia. Speed of senescence progression, effects of ethylene signalling perturbation, and patterns of ethylene biosynthesis gene expression differed across three dahlia cultivars (‘Sylvia’, ‘Karma Prospero’ and ‘Onesta’) suggesting differences in the role of ethylene in their floral senescence, while effects of exogenous cytokinin were less cultivar-specific.